Respuesta :
━━━━━━━☆☆━━━━━━━
▹ Answer
D. 3x² + 13x - 56
▹ Step-by-Step Explanation
(x + 7)(3x - 8) (Using FOIL method)
x * 3x - 8x + 7 * 3x - 7 * 8
3x² - 8x + 7 * 3x - 7 * 8
3x² - 8x + 21x - 56
3x² + 13x - 56
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer:
[tex] \boxed{\sf D. \ 3 {x}^{2} + 13x - 56} [/tex]
Step-by-step explanation:
[tex] \sf Expand \: the \: following: \\ \sf \implies (x + 7)(3x - 8) \\ \\ \sf \implies x(3x - 8) + 7(3x - 8) \\ \\ \sf \implies (x)(3x) - (x)(8) + (7)(3x) - (7)(8) \\ \\ \sf (x)(3x) = 3 {x}^{2} : \\ \sf \implies \boxed{ \sf 3 {x}^{2}} - 8x + (7)(3x) - (7)(8) \\ \\ \sf 7 \times 3 = 21 : \\ \sf \implies 3 {x}^{2} - 8x + \boxed{ \sf 21}x - (7)(8) \\ \\ \sf 7 \times 8 = 56 : \\\sf \implies 3 {x}^{2} - 8x + 21x - \boxed{ \sf 56} \\ \\ \sf 21x - 8x = 13x : \\ \sf \implies 3 {x}^{2} + 13x - 56[/tex]